Neural network approach to collision free path planning for robotics manipulators - Ruano, Antonio (2013)
Abstract: The paper deals with collision free path planning for industrial robotic manipulators. A new efficient algorithm is proposed that is based on a topologically ordered neural network model. This model describes harmonic potential field of the robot configuration space, sampled by non-regular grid. The algorithm has been successfully applied to the off-line programming of a robotic manufacturing cell for the automotive industry.